2012
DOI: 10.2174/157340312803760811
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Apnea and Atrial Fibrillation; 2012 Update

Abstract: Atrial fibrillation (AF) and obstructive sleep apnea (OSA) are very prevalent diseases in modern society. Recent years have seen the emergence of a wide body of literature suggesting an important association between these two diseases. This review will provide a summary of this evidence as it currently exists. First, it will review the literature suggesting an association between AF and OSA by highlighting the prevalence of AF in OSA, the correlation of AF prevalence with OSA severity and the trend towards inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
4

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(30 citation statements)
references
References 76 publications
2
24
0
4
Order By: Relevance
“…6.5.2), ablację AF powinno się oferować otyłym pacjentom w połączeniu z modyfikacjami stylu życia prowadzącymi do redukcji masy ciała. [304,305]. Do występowania AF u pacjentów z obturacyjnym bezdechem sennym może się przyczyniać wiele mechanizmów patofizjologicznych, w tym dysfunkcja autonomiczna, hipoksja, hiperkapnia oraz zapalenie [96,[304][305][306][307].…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
See 1 more Smart Citation
“…6.5.2), ablację AF powinno się oferować otyłym pacjentom w połączeniu z modyfikacjami stylu życia prowadzącymi do redukcji masy ciała. [304,305]. Do występowania AF u pacjentów z obturacyjnym bezdechem sennym może się przyczyniać wiele mechanizmów patofizjologicznych, w tym dysfunkcja autonomiczna, hipoksja, hiperkapnia oraz zapalenie [96,[304][305][306][307].…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
“…[304,305]. Do występowania AF u pacjentów z obturacyjnym bezdechem sennym może się przyczyniać wiele mechanizmów patofizjologicznych, w tym dysfunkcja autonomiczna, hipoksja, hiperkapnia oraz zapalenie [96,[304][305][306][307]. Obturacyjny bezdech senny nasila zmiany ciśnienia wewnątrz klatki piersiowej, które same oraz za pośrednictwem aktywacji nerwu błędnego mogą prowadzić do skrócenia potencjału czynnościowego w przedsionkach i wywoływać AF.…”
Section: Ablacja Przezcewnikowa U Otyłych Pacjentówunclassified
“…304,305 Multiple pathophysiological mechanisms can contribute to AF in obstructive sleep apnoea, including autonomic dysfunction, hypoxia, hypercapnia, and inflammation. 96,304 -307 Obstructive sleep apnoea exaggerates intrathoracic pressure changes, which in itself and via vagal activation can provoke shortening of the atrial action potential and induce AF.…”
Section: Chronic Obstructive Pulmonary Disease Sleep Apnoea and Othmentioning
confidence: 99%
“…On the other hand, prolonged QRS duration is an independent predictor of mortality and cardiovascular diseases (e.g., hypertension and heart failure) in OSAS patients. It has also been shown that severe OSAS patients (AHI ≥ 30) have a four-fold higher frequency of atrial fibrillation (AF) (8). Arrhythmia and its improvement with continuous positive airway pressure (CPAP) therapy in OSAS patients have been reported as well (8).…”
Section: O Bstructive Sleep Apnea Syndrome (Osas) Is a Common Sleep Dmentioning
confidence: 99%
“…It has also been shown that severe OSAS patients (AHI ≥ 30) have a four-fold higher frequency of atrial fibrillation (AF) (8). Arrhythmia and its improvement with continuous positive airway pressure (CPAP) therapy in OSAS patients have been reported as well (8). However, the relationship between OSAS and intrinsicoid deflection (ID) (i.e., R-wave peak time) is unknown.…”
Section: O Bstructive Sleep Apnea Syndrome (Osas) Is a Common Sleep Dmentioning
confidence: 99%